In vitro and in vivo studies on nanocrystalline Ti fabricated by equal channel angular pressing with microcrystalline CP Ti as control1. Issue 6 (27th November 2012) - Nie, F. L.; Zheng, Y. F.; Wei, S.C.; Wang, D. S.; Yu, Z. T.; Salimgareeva, G. K.; Polyakov, A. V.; Valiev, R. Z.
Abstract: Bulk nanocrystalline Ti bars (Grade 4, ϕ4 × 3000 mm 3 ) were massively fabricated by equal channel angular pressing (ECAP) via follow‐up conform scheme with the microcrystalline CP Ti as raw material. Homogeneous nanostructured crystals with the average grain size of 250 nm were identified for the ECAPed Ti, with extremely high tensile/fatigue strength (around 1240/620 MPa) and adorable elongation (more than 5%). Pronounced formation of bonelike apatite for the nanocrystalline Ti group after 14 days static immersion in simulated body fluids (SBF) reveals the prospective in vitro bioactive capability of fast calcification, whereas an estimated 17% increment in protein adsorption represents good bioaffinity of nanocrystalline Ti. The documentation onto the whole life circle of osteoblast cell lines (MG63) revealed the strong interactions and superior cellular functionalization when they are co‐incubated with bulk nanocrystalline Ti sample. Moreover, thread‐structured specimens were designed and implanted into the tibia of Beagles dogs till 12 weeks to study the in vivo responses between bone and metallic implant made of bulk nanocrystalline Ti, with the microcrystalline Ti as control. For the implanted nanostructured Ti group, neoformed bone around the implants underwent the whole‐stage transformation proceeding from originally osteons or immature woven bone to mature lamellar bone (skeletonic trabecular), even with the remodeling being finished till 12 weeks. The phenomenal osseointegration of direct implant‐bone contact can be revealed from the group of the ECAPed Ti without fibrous tissue encapsulation in the gap between the implant and autogenous bone. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.